Marrying Traditions and Maturitas: Examining Law No. 16/2019 in the Context of Islamic Law and Indonesian Social Dynamics - Sa’adah; Zainal Muttaqin; Rusdiyah Faruk (Pascasarjana UIN ANTASARI Banjarmasin, 2022)
Child marriage remains a persistent social challenge in Indonesia. Law Number 16 of 2019, amending the 1974 Marriage Law, emerged from complex social and legal dynamics. This paper investigates the interplay between these dynamics and Islamic legal principles. It examines the high prevalence of child marriage and divorce, alongside existing legal frameworks and their alignment with global norms like human rights, equality, and child protection. By analyzing these factors, the paper sheds light on the motivations behind Law No. 16/2019. The law serves not only as a control mechanism but also potentially as a tool for social reconstruction, aiming to foster a more progressive Indonesian society that prioritizes the maturitas (maturity) of individuals entering marriage.